Anticancer effect of celastrol on human triple negative breast cancer: Possible involvement of oxidative stress, mitochondrial dysfunction, apoptosis and PI3K/Akt pathways - Shrivastava, Shweta; Jeengar, Manish Kumar; Reddy, V. Sudhakar; Reddy, G. Bhanuprakash; Naidu, V.G.M. (Experimental and molecular pathology, 2015)
Signaling via the phosphatidylinositol-3 kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) is crucial for divergent physiological processes including transcription, translation, cell-cycle progression and apoptosis. The aim of work was to elucidate the anti-cancer effect of celastrol and the signal transduction pathways involved. Cytotoxic effect of celastrol was assessed by MTT assay on human triple negative breast cancer cells (TNBCs) and compared with that of MCF-7. Apoptosis induction was determined by AO/EtBr staining, mitochondrial membrane potential by JC-1, Annexin binding assays and modulation of apoptotic proteins and its effect on PI3K/Akt/mTOR pathway by western blotting. Celastrol induced apoptosis in TNBC cells, were supported by DNA fragmentation, caspase-3 activation and PARP cleavage. Meanwhile, celastrol triggered reactive oxygen species production with collapse of mitochondrial membrane potential, down-regulation of Bcl-2 and up-regulation of Bax expression. Celastrol effectively decreased PI3K 110α/85α enzyme activity, phosphorylation of Aktser473 and p70S6K1 and 4E-BP1. Although insulin treatment increased the phosphorylation of Aktser473, p70S6K1, 4E-BP1, celastrol abolished the insulin mediated phosphorylation. It clearly indicates that celastrol acts through PI3k/Akt/mTOR axis. We also found that celastrol inhibited the Akt/GSK3β and Akt/NFkB survival pathway. PI3K/Akt/mTOR inhibitor, PF-04691502 and mTOR inhibitor rapamycin enhanced the apoptosis-inducing effect of celastrol. These data demonstrated that celastrol induces apoptosis in TNBC cells and indicated that apoptosis might be mediated through mitochondrial dysfunction and PI3K/Akt signaling pathway. •Celastrol induces growth inhibition and apoptosis in human triple negative breast cancer.•Celastrol caused cell cycle arrest and mitochondrial dysfunction and inhibited PI3K/Akt pathway.•Celastrol may be a multi-target drug in the treatment of human triple negative breast cancer.